2016
DOI: 10.1016/j.ydbio.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Dynamitin in testes significantly decreased male fertility in Drosophila melanogaster

Abstract: Dynamitin (Dmn) is a major component of dynactin, a multiprotein complex playing important roles in a variety of intracellular motile events. We previously found that Wolbachia bacterial infection resulted in a reduction of Dmn protein. As Wolbachia may modify sperm in male hosts, we speculate that Dmn may have a function in male fertility. Here we used nosGal4 to drive Dmn knock down in testes of Drosophila melanogaster to investigate the functions of Dmn in spermatogenesis. We found that knockdown of Dmn in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Ubiquitous reduction in p24‐2 levels in adults did not affect female fecundity but decreased male fertility in Drosophila (Saleem et al ., ); however, the underlying mechanism remains unclear. Wolbachia affects many transport‐associated molecules in male hosts (Zheng et al ., ; Yuan et al ., ; Wu et al ., ) and thus affects spermatogenesis. Therefore, Wolbachia infection may result in a reduction of ocn expression, thereby reducing p24‐2 expression, and affecting spermatogenesis by reducing vesicular transport activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ubiquitous reduction in p24‐2 levels in adults did not affect female fecundity but decreased male fertility in Drosophila (Saleem et al ., ); however, the underlying mechanism remains unclear. Wolbachia affects many transport‐associated molecules in male hosts (Zheng et al ., ; Yuan et al ., ; Wu et al ., ) and thus affects spermatogenesis. Therefore, Wolbachia infection may result in a reduction of ocn expression, thereby reducing p24‐2 expression, and affecting spermatogenesis by reducing vesicular transport activity.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have demonstrated that Wolbachia significantly modify host sperm and affect fertility (Serbus et al ., ; Yuan et al ., ; Wu et al ., ). However, the potential molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Wolbachia have been estimated to be the most ubiquitous endosymbiont, and can be used as an ideal model for studying the interactions between microbials and their hosts (Werren, 1997;Wu et al, 2016;Bhattacharya et al, 2017;Pan et al, 2018). So far, most studies on Wolbachia focus on the regulatory mechanisms by which Wolbachia mediate host reproduction (Zheng et al, 2011a(Zheng et al, , 2011bLiu et al, 2014;Beckmann et al, 2017;LePage et al, 2017;Bonneau et al, 2018;Shropshire et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evidences have demonstrated that vesicle trafficking plays an important role during spermiogenesis. A number of vesicle trafficking factors are required for the deposition of actin and new membrane during individualization and elongation (Kracklauer et al, ; Wu et al, ). Therefore we explored the expressions of three cytoskeleton‐associated genes: Arp53D (coding for actin‐related protein), CG9313 (related to microtubule‐based movement), and βTub85D (coding for β‐Tubulin at 85D, also called β2‐tubulin).…”
Section: Resultsmentioning
confidence: 99%